2021
DOI: 10.1159/000514648
|View full text |Cite
|
Sign up to set email alerts
|

Cell-Free Circulating Tumor DNA Improves Standard Genotyping of Non-Small-Cell Lung Cancer and Increases Detection of Targetable Alterations in a Selected Hispanic Cohort

Abstract: <b><i>Background:</i></b> Several studies have shown that the non-small-cell lung cancer (NSCLC) genomic background among Hispanics differs from other populations. The finding of low-frequency genomic alterations in cell-free DNA (cfDNA) can increase diagnostic accuracy and could improve treatment in NSCLC. <b><i>Methods:</i></b> Data from 54 Hispanic patients with advanced NSCLC with high clinical suspicion for <i>ALK</i>, <i>EGFR</i>, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Clinically actionable GAs can also be identified by testing blood for circulating tumor DNA (ctDNA), colloquially known as liquid biopsy. 5 Liquid biopsy may identify GAs missed by tissue biopsy [6][7][8][9] and patients benefit similarly from therapies that target GAs identified by either method. 7,[10][11][12] Liquid biopsy has been endorsed by European Society for Medical Oncology and International Association for the Study of Lung Cancer 1,2,13 and is clearly indicated when tissue genotyping fails.…”
Section: Introductionmentioning
confidence: 99%
“…Clinically actionable GAs can also be identified by testing blood for circulating tumor DNA (ctDNA), colloquially known as liquid biopsy. 5 Liquid biopsy may identify GAs missed by tissue biopsy [6][7][8][9] and patients benefit similarly from therapies that target GAs identified by either method. 7,[10][11][12] Liquid biopsy has been endorsed by European Society for Medical Oncology and International Association for the Study of Lung Cancer 1,2,13 and is clearly indicated when tissue genotyping fails.…”
Section: Introductionmentioning
confidence: 99%